The Tragic End of the Czech Footnote - Nodl, Martin (Dějiny – teorie – kritika, 2019)
In historiography, footnotes have gained a distinct role. Works without footnotes are not considered scientific or erudite to such an extent that absence of footnotes disqualifies a book from being accepted as academically respectable. This is, however, the outcome of a long development and in the Czech environment, footnotes have over the past almost two centuries undergone various changes and transformations. In recent decades, however, the Czech academic environment had undergone extensive development linked to the foundation of various regional universities, massive increase in student numbers, increased numbers of qualification theses and persons with higher academic titles. This led to an overproduction of historiographic works, which in turn had an impact on the form of footnotes. In some respects, one could say that footnotes as such became suspect, which in late 2018 and early 2019 led to an absurd debate on whether copying the footnotes from another author amounts to plagiarism or not. In this contribution, which is intended as a contribution to a discussion on this subject, the author tries to trace the development of footnotes in Czech medievalist historiography from the time of František Palacký, through their transformation by the ‘Goll’s school’, the impact of Marxist historiography, and various attempts at revising the importance of footnotes in Czech historiography after 1989. In conclusion, the author offers twenty subjective thoughts on the tragic fate of the Czech footnotes.